2019
DOI: 10.5205/1981-8963.2019.240179
|View full text |Cite
|
Sign up to set email alerts
|

Aromaterapia para a ansiedade e estresse de professores de enfermagem

Abstract: Objetivo: investigar a efetividade do uso da aromaterapia com os óleos essenciais de lavanda (Lavandula angustifolia) ou ylang-ylang (Cananga odorata), associada à massagem, para o alívio da ansiedade e do estresse. Método: trata-se de um estudo quantitativo, exploratório-descritivo e correlacional com delineamento quase-experimental do tipo antes e depois. Realizou-se uma intervenção com seis sessões de massagem com aromaterapia com 21 professores de enfermagem verificado por meio de parâmetros psicológicos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Dhikr relaxation therapy influenced the decrease in anxiety levels, which could calm the soul so that the elderly feel more relaxed in carrying out their daily activities. 17 Moreover, the result of the statistical test of this study indicated that the intervention of Cananga aromatherapy and dhikr provided a relaxing or calming effect; thus, there was a significant difference in reducing anxiety at pre and post-intervention. Meanwhile, the result of the comparative analysis in this study indicated that the intervention of Cananga aromatherapy and dhikr both affected decreasing anxiety levels in elderly with hypertension in the Posyandu Tawarsari Wonosari Gunungkidul.…”
Section: Original Articlementioning
confidence: 68%
“…Dhikr relaxation therapy influenced the decrease in anxiety levels, which could calm the soul so that the elderly feel more relaxed in carrying out their daily activities. 17 Moreover, the result of the statistical test of this study indicated that the intervention of Cananga aromatherapy and dhikr provided a relaxing or calming effect; thus, there was a significant difference in reducing anxiety at pre and post-intervention. Meanwhile, the result of the comparative analysis in this study indicated that the intervention of Cananga aromatherapy and dhikr both affected decreasing anxiety levels in elderly with hypertension in the Posyandu Tawarsari Wonosari Gunungkidul.…”
Section: Original Articlementioning
confidence: 68%
“…Além disso, a pesquisa apontou a diminuição de parâmetros como PA e FC, visto que esse último apresentou diminuição em todas as sessões de aromaterapia. Porém, é destacado em tal estudo que por mais que se observe tal redução, a mesma não atinge níveis de significância estatística (Dias et al 2019).…”
Section: Discussionunclassified
“…Na oficina foi mostrada, também, a Aromaterapia, que visa reintegrar o equilíbrio corpóreo com a utilização de óleos essenciais (OEs) 100% puros extraídos de plantas aromáticas (Dias et al, 2019;Camargo & Carvalho, 2019). É uma prática terapêutica com benefícios devido aos constituintes químicos característicos e particulares de cada OE, a fim de promover e melhorar a saúde, o bem-estar, a higiene e a estética (Freitag & Badke, 2019;Pessoa et al, 2021).…”
Section: A Oficina De Autocuidado Por Meio Das Práticas Integrativas ...unclassified